The Ethnic Diversity and Collective Action Survey (EDCAS): Technical report - Merlin Schaeffer; Ruud Koopmans; Susanne Veit; Mareike Wagner; Jonas Wiedner (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
The EDCA-Survey is a large scale CATI telephone survey conducted in three countries: Germany, France and the Netherlands. The survey was designed to test theoretical arguments on the effects of ethnic diversity on social capital and civic engagement. This aim demands for a sophisticated design. The survey is not representative for the entire populations of Germany, France or the Netherlands. Instead, the basic population is the population over the age of 18 in 74 selected regions in Germany, France and the Netherlands that have sufficient language skills to conduct an interview in the language of their country of residence, or in the case of the oversample of people with Turkish migration background to conduct the interview in Turkish. The aim of the survey is to enable the comparison of these 74 regions, which vary on contextual characteristics of interest. In addition, the EDCA-Survey includes one oversample of migrants in general (24%) and an additional second oversample of Turkish migrants in particular (14%). The oversampling is the same within each of the 74 regions, each of which has about 100 observations and seven specially chosen cities even 500. This survey design is an important characteristic of the EDCA-Survey and distinguishes it from other available data. This is important since one aim of the EDCA-Survey is to enable the aggregation of contextual characteristics from the survey itself. Overall, 10.200 completed interviews were conducted - 7500 in Germany, 1400 in France and 1300 in the Netherlands. – – Der EDCA-Survey ist eine CATI gestützte Telefonumfrage, die in Deutschland, Frankreich und den Niederlanden durchgeführt wurde. Die Umfrage wurde mit dem Ziel erhoben, Effekte ethnischer Diversität auf Sozialkapital und Zivilengagement zu untersuchen. Dieses Vorhaben setzt ein komplexes Surveydesign voraus. So ist die Umfrage nicht repräsentativ für die Bevölkerungen von Deutschland, Frankreich und den Niederlanden. Stattdessen bildet die Grundgesamtheit die Bevölkerung von 74 ausgewählten Regionen der drei Länder, die über die Sprachfertigkeit verfügen, ein Interview in der Landessprache oder gegebenenfalls auf Türkisch zu führen. Ziel ist der Vergleich dieser 74 Regionen, die sich hinsichtlich verschiedener Charakteristika unterscheiden. Darüber hinaus weist der EDCA-Survey eine überproportionale Stichprobe von Personen mit Migrationshintergrund (24%) und eine zweite überproportionale Stichprobe von Personen mit türkischem Migrationshintergrund (14%) auf. Diese überproportionale Stichprobe wurde in jeder der 74 Regionen gezogen, in denen jeweils ca. 100 Interviews durchgeführt wurden. In sieben speziell ausgesuchten Regionen wurden 500 Interviews geführt. Dieses Surveydesign ist ein zentrales Charakteristikum des EDCA-Surveys und ermöglicht die Aggregation von Kontextmerkmalen aus dem Survey. Insgesamt wurden 10.200 vollständige Interviews erhoben - 7500 in Deutschland, 1400 in Frankreich und 1300 in den Niederlanden.
Keywords: 300